Exploring the Uses, Constraints and Opportunities of ICT for Citizen Participation in Governance - Martin, Edwin S.; Cabo, Wilhelmina L.; Nicolas, Eleanor E. (Philippine Journal of Public Administration, 2017)
ICT in governance is a growing field. Using the results of an exploratory study on ICT utilization for participation in the country, this paper discusses the types of ICTs that are used for e-participation, emerging themes, contents and purposes of ICT usage, and the constraints or barriers in the use of ICTs for e-participation. It also explores the effectiveness of ICTs as tools for participation and suggests directions to further enhance the potentials of ICT for participation. While some constraints and problems associated with the use of ICT in relating with government were pointed out, for instance, bandwidth connection and the lack of knowledge on the basics of ICT use, there is much use of ICT particularly through the internet and mobile phones in accessing and sharing information and monitoring government performance. NGOs particularly have found the internet as an effective mechanism for mobilization and advancing their advocacy. The findings highlight the potential of ICT as mechanism for bridging government and citizen and at the same time point to the barriers that must be overcome in order to take full advantage of its uses in enhancing citizen-state relations.
Keywords: ICT, e-democracy, e-governance, e-participation, ICT in governance